Animal Rationality Later Medieval Theories 1250-1350 - Oelze, Anselm (Investigating Medieval Philosophy, 2018)
In Animal Rationality: Later Medieval Theories 1250-1350, Anselm Oelze offers the first comprehensive and systematic exploration of theories of animal rationality in the later Middle Ages. Readership: Everyone interested in medieval philosophy and psychology in general, as well as the history of the concept of animal rationality and of the animal/human boundary in particular.